2015
DOI: 10.1055/s-0035-1564797
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Premature, Very Low-Birth-Weight Infants

Abstract: The epidemiology of neonatal acute kidney injury (AKI) is not well established, partly due to lack of a consensus definition. Preterm neonates are likely especially vulnerable to AKI. We performed a retrospective review to assess the incidence of and risk factors for AKI in very low-birth-weight (VLBW), premature infants admitted to a level 4 NICU (2006?2007). AKI was classified using a standardized definition based on changes in serum creatinine (SCr). AKI incidence varied inversely with gestational age (GA):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…This study revealed that early GA was significantly associated with an increased risk of AKI in VLBW infants. This finding is consistent with the observations by Carmody et al ( 8 ) and Mian et al ( 10 ). This may be attributed to the fact that the earlier the GA, the lesser is the number of nephrons and their maturity ( 23 ), which leads to an increased susceptibility toward kidney injury ( 24 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study revealed that early GA was significantly associated with an increased risk of AKI in VLBW infants. This finding is consistent with the observations by Carmody et al ( 8 ) and Mian et al ( 10 ). This may be attributed to the fact that the earlier the GA, the lesser is the number of nephrons and their maturity ( 23 ), which leads to an increased susceptibility toward kidney injury ( 24 ).…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the incidence of AKI has been reported to be high, at 12–40% ( 5 8 ), which makes it particularly important to identify the potential predictors for AKI and develop a risk prediction model for the early detection of AKI in VLBW infants ( 9 ). Mian et al retrospectively analyzed the clinical data of a cohort of 266 VLBW infants and found that early gestational age (GA), patent ductus arteriosus (PDA), and prolonged mechanical ventilation were independent predictors for AKI in VLBW infants ( 10 ). Al Malla et al in their retrospective study of 293 VLBW infants, observed that necrotizing enterocolitis (NEC) was an independent predictor for AKI in VLBW infants ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Single-center studies have reported rates of AKI from 12% to 40%, and only the creatinine criterion was used in most of the series, which is in contradiction with the methodology behind the neonatal KDIGO AKI definition (16)(17)(18). In the recently published multicentric Extremely Low Gestational Age Newborns study, which included 923 extreme preterm neonates (,28 weeks), the prevalence of early-onset AKI was low (12%) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies confirm the association between AKI and mortality, a retrospective cohort study of 266 premature (<32 weeks gestation) and very low birthweight (<1500 g) neonates found no such association (13). The incidence of AKI in this study was higher than we report, with 65% of 22–25-week extremely low gestational age neonates developing AKI, and 25% of neonates born at a gestational age of 26–28 weeks.…”
Section: Discussionmentioning
confidence: 99%